2014
DOI: 10.1063/1.4892530
|View full text |Cite
|
Sign up to set email alerts
|

How well-connected is the surface of the global ocean?

Abstract: The Ekman dynamics of the ocean surface circulation is known to contain attracting regions such as the great oceanic gyres and the associated garbage patches. Less well-known are the extents of the basins of attractions of these regions and how strongly attracting they are. Understanding the shape and extent of the basins of attraction sheds light on the question of the strength of connectivity of different regions of the ocean, which helps in understanding the flow of buoyant material like plastic litter. Usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
153
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(165 citation statements)
references
References 37 publications
11
153
0
Order By: Relevance
“…30 Using the global drifter data set, the FCM method was able to identify global ocean partitioning results similar to those found using transfer operator methods. 33 While the FCM method is quite robust for sparse and intermittent data, there are some limitations. The approach limits the consideration of relative movement between trajectories to just the prescribed distance metric.…”
Section: A Cluster Based Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…30 Using the global drifter data set, the FCM method was able to identify global ocean partitioning results similar to those found using transfer operator methods. 33 While the FCM method is quite robust for sparse and intermittent data, there are some limitations. The approach limits the consideration of relative movement between trajectories to just the prescribed distance metric.…”
Section: A Cluster Based Analysismentioning
confidence: 99%
“…A related study used the transfer operator to divide the ocean into distinct regions, in an attempt to quantify the connectivity of different parts of the ocean. 33 To better represent the ocean surface dynamics, this study allowed for the loss of trajectories by considering an open domain, which accounted for the beaching of trajectories and advection to the poles. By considering by the Perron-Frobenius operator and its dual, the Koopman operator, the study was extended to both forwards and backwards time, which allowed identification of regions of upwelling and downwelling in the ocean.…”
Section: Applications Of the Probabilistic Approachmentioning
confidence: 99%
“…[23] it was shown that, under the standard approximation of Markovian dynamics (i.e. P(t 0 , τ 1 +τ 2 ) ≈ P(t 0 , τ 1 )P(t 0 + τ 1 , τ 2 )) [28,29,45]), for velocity fields either steady or periodic with period T , and for values of τ multiple of T , C c i is non-zero at nodes containing the position at time t 0 of a periodic trajectory of period 3τ . In open flows, periodic orbits can only appear on the non-escaping set, i.e.…”
Section: The Network Approachmentioning
confidence: 99%
“…In oceanographic flows, particle retention has been assessed with tools derived from dynamical systems theory (e.g., Castiglione et al, 1999;Cencini et al, 1999); the attractive properties of Lagrangian coherent structures may play an important trapping role (Peacock and Haller, 2013; for a Mediterranean application see Rossi et al, 2014). Froyland et al (2014) quantitatively assessed the location and effectiveness of particle attraction areas in the world ocean on the basis of synthetic Lagrangian trajectories interpreted in a Markovian approximation. Here we will limit ourselves to the most straightforward accumulation definition, i.e., a mediumand/or long-term local increase of FLP density (see also below, Section Lagrangian Transport Reconstruction).…”
Section: Figure 6 | Pseudoeulerian Kinetic Energies: Extended Winter mentioning
confidence: 99%